Analisis Lingkungan Positif yang Mendukung Pembelajaran Pada Jenjang Sekolah Dasar - Labibah Alfiatin Nafi’ah; Maharani Desita Eka Cahyani; Ayasha Nabila Audiya Nency; Faizah Reva Abidah; Nazira Syifa Hadyan (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2024)
This study aims to explore the importance of the learning environment to students' learning performance. Every school, especially teachers, must try to provide the best environment for students so that they have high intentions and enthusiasm for learning. The type of approach used in this study is qualitative which is carried out by survey methods, interviews with teachers, and questionnaires from students in a structured manner. The subject of the study was taken from one of the inclusion elementary schools in the Surabaya area, namely SD Negeri Klampis Ngasem 1/246. After conducting surveys and interviews, it can be concluded that to create a positive environment learning is not imposed on teaching staff alone, but there are other supporting factors such as classroom atmosphere, learning facilities, the environment of the students themselves, the role of parent involvement, and an inclusive school culture that plays a significant role in supporting the creation of a positive environment. Teachers must play an important role in creating a positive learning environment supported by an adequate atmosphere and facilities so that students feel comfortable and safe. If the above factors support each other, a positive learning environment will be created so that students can achieve their full potential.